Playing Charades to Boost Young Learners’ English Language Ability - Maghhfirah, Naily (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2024)
The educational environment has an important role in children's language skills, English. Schools or other educational institutions are expected to be able to cultivate, grow, and develop the language skills of their students. MI Miftahul Ulum, Sucolor, Maesan, Bondowoso is an educational institution that is aware of the importance of developing children's language skills and takes part in building the character of their students, especially in terms of language skills. MI Miftahul Ulum applies a word guessing game to each student in developing English skills. The aim of this activity is that students can at least say words or speak English. This study aims to reveal and describe how the word guessing game is implemented at MI Miftahul Ulum in an effort to improve children's English skills. In addition, this study intends to find out how and to what extent the contribution of charades games can improve English skills, especially MI Miftahul Ulum students. Therefore, based on the research objectives, the researcher applied a qualitative descriptive method. Data collection techniques applied include observation, documentation, and interviews. Meanwhile, the informants in this study involved school principals, teacher boards, and MI Miftahul Ulum students. From this study, the results were obtained that by implementing the word guessing game, students were able to say and even speak English (mix) well, as well as their pronunciation, now they are slowly being able to say even speak English correctly when asked. For students who can't yet, they can easily learn through what they hear when playing charades. The application of the word guessing game at MI Miftahul Ulum is used to evaluate children's ability to practice speaking English which focuses on the synergy between what is heard and the pronunciation. The game is carried out routinely, the goal is that with an intensive evaluation intensity, MI Miftahul Ulum students experience very rapid development and can mention English vocabulary in mixed English speaking.